Учинення ризикованих дій як підстава притягнення до відповідальності посадових осіб підприємницького товариства - Жорнокуй, В. Г.; Zhornokui, V. H.; Жорнокуй Валентина Григорівна (Право і безпека. – 2022. – № 3 (86). – С. 70-80, 2022)
З’ясовано сутність ризикованих дій як підстави притягнення до відповідальності посадових осіб підприємницького товариства. Підкреслено, що з урахуванням сутності ризикової діяльності підприємницького товариства, спрямованої на отримання прибутку та подальшого його розподілу між учасниками, в діях (бездіяльності) учасників відносин у межах відповідного виду юридичної особи присутніми є ризики як економічного, так і юридичного змісту. Такі ризики слід класифікувати на виправдані та невиправдані, що першочергово пов’язується з подальшою можливістю притягнення до відповідальності осіб, винних у заподіянні шкоди учасникам корпоративних правовідносин. Наголошено, що саме виправданий характер підприємницького ризику в діях осіб, які виконують функції органів підприємницького товариства, та їх розумна, добросовісна, з належною дбайливістю й обачністю діяльність, а також ужиття всіх заходів для належного виконання обов’язків та запобігання несприятливих правових наслідків для товариства дозволяє говорити про звільнення їх від відповідальності за завдані збитки.

On the basis of the conducted analysis, it has been concluded that the responsibility of the officials of entrepreneurial companies in modern law is studied in the context of corporate governance as one of the elements of the management and control system of companies and one of the means of ensuring their responsible management. At the same time, the issue of clear delimitation of powers between the bodies of an entrepreneurial company is closely related to the issue of liability of their officials to the company itself, since their liability always arises as a result of violation of the duties assigned to a particular body (to one or another official). It is the specific definition of the rights and obligations of persons performing the functions of the bodies of a business company, and their activities on behalf of the company in good faith and reasonably and without exceeding their powers that forms the basis for the stability of property and non-property corporate relations within the corporate governance of a business company. The essence of risky actions as grounds for bringing to responsibility of officials of an entrepreneurial company has been clarified. It has been concluded that, given the essence of the risky activities of an entrepreneurial company aimed at making a profit and its further distribution among the participants, the actions (inaction) of the participants of relations within the relevant legal entity contain risks of both economic and legal content. Such risks should be classified into justified and unjustified, which are associated with the further possibility of bringing to justice the persons guilty of causing damage to the participant of corporate legal relations. It has been emphasized that it is the justified nature of entrepreneurial risk in the actions of persons performing the functions of the bodies of an entrepreneurial company, and their reasonable, conscientious, with due care and prudence activity, as well as taking all measures for the proper performance of duties and prevention of adverse legal consequences for the company, allows o talk about their release from liability for damages. It has been noted that the legal mechanism of civil liability of officials to the business company for actions that are risky and may cause damage to the company needs to be improved in domestic law.

Выяснена сущность рискованных действий как основания привлечения к ответственности должностных лиц предпринимательского общества. Подчеркнуто, что с учетом сущности рисковой деятельности предпринимательского общества, направленной на получение прибыли и дальнейшее ее распределение между участниками, в действиях (бездействии) участников отношений в пределах соответствующего вида юридического лица присутствуют риски как экономического, так и юридического содержания. Такие риски следует классифицировать на оправданные и неоправданные, что в первую очередь связывается с дальнейшей возможностью привлечения к ответственности лиц, виновных в причинении вреда участникам корпоративных правоотношений. Отмечено, что именно оправданный характер предпринимательского риска в действиях лиц, выполняющих функции органов предпринимательского общества, и их разумная, добросовестная, с надлежащей заботливостью и осмотрительностью деятельность, а также принятие всех мер по надлежащему исполнению обязанностей и предотвращению неблагоприятных правовых последствий для общества позволяет говорить об освобождении их от ответственности за причиненный ущерб.
Taking risky actions as a basis for prosecuting the officials of the business company
Совершение рискованных действий как основание притягивания к ответственности должностных лиц предпринимательского общества
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; корпоративні правовідносини; corporate legal relations; корпоративные правоотношения; юридична особа; legal entity; юридическое лицо; підприємницьке товариство; business association; предпринимательское общество; відповідальність; responsibility; ответственность; ризик; risk; риск